Scotland's Foreshore : Public Rights, Private Rights and the Crown 1840-2017. - MacAskill, John (Scotland's land, 2017)
Scotland's Foreshore tells the story of the battle that took place during the nineteenth century and into the early twentieth century between the Crown and private proprietors over the ownership of the foreshore.